Chromosomal Differentiation of Deschampsia (Poaceae) Based on Four Satellite DNA Families - González, María Laura; Chiapella, Jorge Oscar; Urdampilleta, Juan Domingo (Frontiers in Genetics, 2021)
Diverse families of satellite DNA (satDNA) were detected in heterochromatin regions of Deschampsia. This kind of repetitive DNA consists of tandem repeat sequences forming big arrays in genomes, and can contribute to lineages differentiation. The differentiation between types of satDNA is related to their sequence identity, the size and number of monomers forming the array, and their chromosomal location. In this work, four families of satDNA (D2, D3, D12, D13), previously isolated by genomic analysis, were studied on chromosomal preparations of 12 species of Deschampsia (D. airiformis, D. antarctica, D. cespitosa, D. cordillerarum, D. elongata, D. kingii, D. laxa, D. mendocina, D. parvula, D. patula, D. venustula, and Deschampsia sp) and one of Deyeuxia (D. eminens). Despite the number of satDNA loci showing interspecific variation, the general distribution pattern of each satDNA family is maintained. The four satDNA families are AT-rich and associated with DAPI + heterochromatin regions. D2, D3, and D12 have mainly subterminal distribution, while D13 is distributed in intercalary regions. Such conservation of satDNA patterns suggests a not random distribution in genomes, where the variation between species is mainly associated with the array size and the loci number. The presence of satDNA in all species studied suggests a low genetic differentiation of sequences. On the other hand, the variation of the distribution pattern of satDNA has no clear association with phylogeny. This may be related to high differential amplification and contraction of sequences between lineages, as explained by the library model.